Methodological characteristics of evaluative studies of drug prevention programs in Brazil: scoping review - Daniela Ribeiro Schneider; Charlene Fernanda Thurow; Tallita Franzoloso; Leila Gracieli da Silva; Guilherme Gomes Silva; Elaine Lucas dos Santos; Liz Paola Domingues; Leila Pimentel dos Anjos; Fernanda Machado Lopes; Ana Regina Noto (Revista Latino-Americana de Enfermagem)
Objective: to map studies that have developed evaluation processes of prevention programs for the use of alcohol and other drugs in Brazil, analyzing their methodological characteristics. Method: a scoping review guided by the Joanna Briggs Institute Manual and the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews. The searches were carried out in eight databases and a theses and dissertations database, screened with double-blind in Rayyan®, analyzed with a focus on the methodology of the evaluative studies and through qualitative synthesis. Results: of the 56 publications included, the majority used an observational design, generally related to process evaluations (n = 26), followed by experimental (n = 23) and quasi-experimental (n = 8) analyses of results in terms of effectiveness and efficacy, respectively. Of the eleven actions analyzed, eight are universal prevention programs, one is selective prevention and two are a preventive strategy. Conclusion: most of the programs evaluated are universal, aimed at adolescents, carried out in schools and focused on various drugs. It is recommended to focus on new groups, such as Indigenous populations and other risk conditions, and to develop selective programs in future government initiatives to prevent drug use in Brazil.